2010
DOI: 10.1074/jbc.m110.117945
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate Receptor 4 Uses HER2 (ERBB2) to Regulate Extracellular Signal Regulated Kinase-1/2 in MDA-MB-453 Breast Cancer Cells

Abstract: We demonstrate here that the bioactive lipid sphingosine 1-phosphate (S1P) uses sphingosine 1-phosphate receptor 4 (S1P 4 ) and human epidermal growth factor receptor 2 (HER2) to stimulate the extracellular signal regulated protein kinase 1/2 (ERK-1/2) pathway in MDA-MB-453 cells. This was based on several lines of evidence. First, the S1P stimulation of ERK-1/2 was abolished by JTE013, which we show here is an S1P 2/4 antagonist and reduced by siRNA knockdown of S1P 4 . Second, the S1P-stimulated activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 36 publications
4
76
0
Order By: Relevance
“…S1PR2 expression was lower in the ALDH-positive cell population compared with MCF-7 cells, and other types of S1PR are yet to be detected in MCF-7 cells ( Supplementary Fig. 2) 19,20 . Stimulation with S1P increased the proportion of ALDH-positive cell population in a dose-dependent manner, with a maximal response observed at 100 nM (Fig.…”
mentioning
confidence: 96%
“…S1PR2 expression was lower in the ALDH-positive cell population compared with MCF-7 cells, and other types of S1PR are yet to be detected in MCF-7 cells ( Supplementary Fig. 2) 19,20 . Stimulation with S1P increased the proportion of ALDH-positive cell population in a dose-dependent manner, with a maximal response observed at 100 nM (Fig.…”
mentioning
confidence: 96%
“…Long et al, in their study on cell lines, reported that S1P4 induced cellular migration. 21 In the literature, there was no study clarifying the high levels of S1P4 gene expression in neuroblastoma patients. The interaction between various cancer cell types and S1P4 gene expression are described in various studies of cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inhibition of SphK1 reduced S1P/S1P4-induced activation of ERK1/2 and altered HER2 trafficking in these cells [18]. Furthermore, inhibition of SphK1 reduced and treatment with a S1P 4 agonist, phyto-S1P, stimulated ERK activation via a mechanism that involves HER2, suggesting synergistic interactions between S1P 4 and HER2 in these cells [18,69]. In contrast to the findings in ER-positive cells where HER2 and SphK1 interact in a negative feedback mechanism to induce tolerance against cancer progression, the interactions of SphK1, S1P and S1P 4 with HER2 suggest sphingolipids act together with HER2 to enhance ER-negative breast cancer progressions.…”
Section: Her2 Type: Er-negative and Her2-positivementioning
confidence: 95%
“…These cells express abundant S1P 3 , small quantities of S1P 2/4 and very limited S1P 1/5 . Despite predominant expression of S1P 3 , the less abundant S1P 4 interact with HER2 to regulate S1P-induced ERK [69]. This was evidenced by reduced S1P-stimulated ERK activity through independent downregulation of S1P 4 and HER2 expressions.…”
Section: Her2 Type: Er-negative and Her2-positivementioning
confidence: 99%
See 1 more Smart Citation